City Management in the Era of Knowledge and Technical and Technological Progress After the COVID–19 Pandemic - Stawasz, Danuta (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The article presents considerations related to the necessity of redefining urban policy in the period of civilization overstimulation and the crisis related to the COVID–19 pandemic. The analysis refers to the indication that science and knowledge as well as technical and technological progress create unquestionable opportunities for overcoming crisis situations, such as climate change, related to access to water, obtaining energy, environmental protection or controlling a pandemic. The issue of the necessity of overcoming the resistance of various social groups to the acceptance and implementation of modern ideas and solutions was also raised. The city’s policy should be oriented towards the development of public services, taking into account solutions in line with the smart city concept. The active participation of conscious citizens in deciding on solutions introduced by city authorities is one of the conditions of city development.